ANALISIS PENGARUH PEMUPUKAN TERHADAP TINGKAT KESINTASAN DAN PERTUMBUHAN BIBIT GAHARU (Aquilaria microcarpa Baill.) - Sahromi, Sahromi; Wahyuni, Sri; Pribadi, Didit Okta (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2010)
Treating gaharu (Aquilaria microcarpa) seedlings with inorganic fertilizers is essential to obtain vigorous seeds with high adaptability for establishment on the field. The aims of this research were to find out the effect of fertilization on the survival and growth rate of Aquilaria microcarpa seedlings and to identify appropriate dosage of fertilizer that could increase the growth optimally. Complete Random Design was employed with two treatments i.e. using root fertilizer (Urea, TSP, KCL) with 5 dosage levels and using leaf fertilizer (Gandasil D and Bayfolan) with 7 dosage levels. Data was analyzed by using statistic descriptive and analysis of variance (ANOVA) method. The parameters used were seedling survival rate, height increase and number of leaves. The result showed that the two fertilizers could increase survival rate of the seedling. However, higher dosage of root fertilizer was followed by lower survival rate. The treatment using root fertilizer had a significant effect on the number of leaves, whereas treatment using leaf fertilizer had a significant effect on the increase of the seedling height. Adding leaf fertilizer is considered more useful in terms of survival and growth rate.